Special Education Teacher Education Learning Packages to Increase Knowledge for Sustainable Development - Kasirah, Irah; Maulidina, Citra Ashri; Jaya, Indra; Yusro, Muhammad Najmil (Department of Special Education, 2023)
This research aims to develop an instructional package of Education for Sustainable Development to improve the knowledge of teachers of Special Education about Education for Sustainable Development. The implementation of research in special schools that provide education for mentally disabled students in the East Jakarta area. The research method uses R & D with the development model of Dick and Carey (2009). The sample of the research were teachers of special education who provided learning for mentally disabled students in the East Jakarta area totaling 70 teachers. The sampling technique uses random sampling techniques. Product output is a knowledge textbook of Education for Sustainable Development. The research results show that knowledge books of Education for Sustainable Development can improve teacher knowledge about Education for Sustainable Development.